Compressive behavior and design of octagonal rubberized concrete-filled double steel tubular stub columns stiffened by headed studs. (August 2022) - Ami, Masoud; Zahrai, Seyed Mehdi
Abstract: Today, Rubberized Concrete-Filled Double Steel Tubular (Ru-CFDST) columns are state-of-the-art structures efficiently considered by construction engineers. Recent research shows that using rubberized concrete (RuC) in steel tube columns due to the high elastic properties of rubber increases their ductility and energy absorption capacity. On the other hand, the low modulus of elasticity of the rubber causes a sharp decrease in the bearing capacity of the columns. The main purpose of this article is to adopt a suitable strategy to increase the reduced resistance in such structures. Several parameters including: the width-to-thickness ( Bo /to ) ratio of the outer tube, diameter-to-thickness ( Di /ti ) ratio of the inner tube, the yield strength of the outer tube ( fyOT ) and the inner tube ( fyIT ), two types of concrete (normal concrete (NC) and rubberized concrete (RuC) with rubber content of 10% and 20%), as well as the existence of headed studs in the Ru-CFDST columns with two distances of 50 mm and 100 mm are evaluated. Based on the results, utilizing rubber particles with a content of 20% increases the energy absorption capacity and the ductility of the columns by a maximum of 200% and 70%, respectively. Also, the presence of headed studs and reducing their intervals in the Octagonal Ru-CFDST (O-Ru-CFDST) columns enhance the ultimate strength of the columns by up to 54%. Finally, a new design procedure is proposed to estimate the ultimate load of stiffened and un-stiffened octagonal CFDST stub columns.